Synthesis and Characterization of 9-Phenyl-9H-purin-6-amines from 5-Amino-1-phenyl-1H-imidazole-4-carbonitriles - Asieh Yahyazadeh; Fatemah Habibi (E-Journal of Chemistry)
9-Phenyl-9H-purin-6-amine derivatives have been synthesized in high yields by reaction between 5-amino-1-phenyl-1H-imidazole-4-carbonitrile with HC(OEt)3 and Ac2O followed by reaction with ammonia.